Self-Reported Disability in Adults with Severe Obesity. (26th October 2011) - Kyrou, I.; Osei-Assibey, G.; Williams, N.; Thomas, R.; Halder, L.; Taheri, S.; Saravanan, P.; Kumar, S.
Abstract : Self-reported disability in performing daily life activities was assessed in adults with severe obesity (BMI ≥ 35 kg/m 2 ) using the Health Assessment Questionnaire (HAQ). 262 participants were recruited into three BMI groups: Group I: 35–39.99 kg/m 2 ; Group II: 40–44.99 kg/m 2 ; Group III: ≥45.0 kg/m 2 . Progressively increasing HAQ scores were documented with higher BMI; Group I HAQ score: 0.125 (median) (range: 0–1.75); Group II HAQ score: 0.375 (0–2.5); Group III HAQ score: 0.75 (0–2.65) (Group III versus II P < 0.001 ; Group III versus I P < 0.001 ; Group II versus I P = 0.004 ). HAQ score strongly correlated with BMI and age. Nearly three-fourths of the study participants reported some degree of disability (HAQ score > 0). The prevalence of this degree of disability increased with increasing BMI and age. It also correlated to type 2 diabetes, metabolic syndrome, and clinical depression, but not to gender. Our data suggest that severe obesity is associated with self-reported disability in performing common daily life activities, with increasing degree of disability as BMI increases over 35 kg/m 2 . Functional assessment is crucial in obesity management, and establishing the disability profiles of obese patients is integral to both meet the specific healthcare needs of individuals and develop evidence-based public health programs, interventions, and priorities.